27Al NMR diffusometry of Al13 Keggin nanoclusters. (14th October 2021) - Graham, Trent R.; Chun, Jaehun; Schenter, Gregory K.; Zhang, Xin; Clark, Sue B.; Pearce, Carolyn I.; Rosso, Kevin M.
Abstract: Although nanometer‐sized aluminum hydroxide clusters (i.e., ϵ‐Al13, [Al13 O4 (OH)24 (H2 O)12 ] 7+ ) command a central role in aluminum ion speciation and transformations between minerals, measurement of their translational diffusion is often limited to indirect methods. Here, 27 Al pulsed field gradient stimulated echo nuclear magnetic resonance (PFGSTE NMR) spectroscopy has been applied to the AlO4 core of the ϵ‐Al13 cluster with complementary theoretical simulations of the diffusion coefficient and corresponding hydrodynamic radii from a boundary element‐based calculation. The tetrahedral AlO4 center of the ϵ‐Al13 cluster is symmetric and exhibits only weak quadrupolar coupling, which results in favorable T 1 and T 2 27 Al NMR relaxation coefficients for 27 Al PFGSTE NMR studies. Stokes–Einstein relationship was used to relate the 27 Al diffusion coefficient of the ϵ‐Al13 cluster to the hydrodynamic radius for comparison with theoretical simulations, dynamic light scattering from literature, and previously published 1 H PFGSTE NMR studies of chelated Keggin clusters. This first‐of‐its‐kind observation proves that 27 Al PFGSTE NMR diffusometry can probe symmetric Al environments in polynuclear clusters of greater molecular weight than previously considered. Abstract : The tetrahedral core of nanometer‐sized aluminum hydroxide nanoclusters exhibits favorably low quadrupolar coupling properties such that 27 Al diffusion is measurable with modern gradient coils. Practical considerations are provided regarding the extension of PFGSTE NMR to other quadrupolar nuclei.